근로자의 구강보건에 대한 인식과 실천정도 조사 - 일개 사업장을 중심으로 - 류다영; 송귀숙; 배수명 (Han'guk Ch'iwisaeng Hakhoe chi, 2010)
Objectives : The purpose of this study was to examine the oral health awareness and practice of workers. Methods : The subjects in this study were 200 workers in a working place located in Taean-gun, Chung-Nam Province. The data for this study was obtained by means of a self-administered questionnaire. Results : 1. An average of awareness for the oral health of workers was 2.60±0.44 points out of 4. They were most aware of the item that toothbrushing should be done after meals(3.06±0.42), and the second most widely recognized item was that toothbrushing should be done before bedtime(2.73±0.60). 2. An average of practice for the oral health of workers was 2.54±0.32 points out of 4. They did the best was brushing their teeth after meals(2.97±0.33), followed by cleaning the tongue during toothbrushing(2.91±0.45). 3. Awareness of oral health was significantly higher in such groups, including the female, college graduates, unmarried(p＜0.05). 4. Practice of oral health was significantly higher in such groups, including the female, college graduates(p＜0.05). Conclusions : To reform and improve of the system, incremental oral health care system for workers is needed. and oral health education is needed to increase the motivation of workers to control their basic dental disease. KCI Citation Count: 15